PENGARUH PENGGUNAAN METODE ROLE PLAYING TERHADAP MINAT BELAJAR SISWA KELAS X PADA MATERI VIRUS DI SMA AZHARYAH PALEMBANG - Munir Munir; Awalul Fatiqin; Ira Kendi (UNIVERSITAS PGRI MADIUN, 2017)
A learning activity that did not correspond with the interest will generated unfavorable achievement. It can be said that with appropriate learning methods can lead to student interst. In learning process we need to caused a learning interest to the students. But in the real class a lot of teachers finds obtacles, because the lack of variations in learning method. Therefore the formulation of the problems is there any affection towards the use of role playing method in student learning interest on tenth grade student of SMA Azharyah palembang, this study aims to determine the effect of the use of the role playing towards the student learning interest of class X on virus material in SMA Azharyah Palembang . this research was done in august until semptember 2016 in SMA Azharyah Palembang. The population of this research was all of X student class of SMA Azharyah Palembang which is divided inti 2 classes and 30 students in average. X1 as a experiment class and X2 as a control class, sampling was done by used sampling jenuh technique. The research was used quantitative research method. The design was used in this research is true experimental design in form of posstest-only control design. To se the interest in students learning is done by using questionnaires and observation sheets. And to measure the effect of role playing method to student learning interst is using t-test. The result show that the learning interst in experiment class in high category was 33%, medium 47% and low 20%. Meanwhile in control class in high category was 20%, medium 50% and low 30% this shows that the experimental class student learning interest is higher compared to the control class. Furthermore there is an influence on students learning interest. Obtained t hitung = 11,75 then compared with t table= 1,671. So the result showed that t hitung > t table. Thus Ha accepted.